Ø£Ø³ÙØ§ÙÙØ¨ Ø§ÙÙÙØ±Ø¢Ù Ø§ÙÙÙØ±ÙÙ ÙÙ Ù ÙÙØ²Ø§ØªÙÙØ§ (Ø¯Ø±Ø§Ø³ÙØ© Ù ÙÙØ§Ø±ÙÙØ© Ø£Ø¯Ø¨ÙÙÙØ©( - Ridha, M. Rasyid (Institut Agama Islam Negeri (IAIN) Palu, 2008)
In the period of JÃ¢hiliyyah, the Arabs always felt proud of their language. They also competed with each other for selecting a particular literary style in expressing their words and beautifying dictions in their poetry and prose. However, when Alquran was revealed, they did not find such literary style as the Qurâanâs. They chose words as refined and perfect as the Qurâanâs. This is one of the driving reasons to study and compare the Qurâanâs literary style and one which has been used so far in Arabic expressions. One of the factors might be that the Qurâanâs literary style covers myriad of meanings.Kata Kunci: Alquran, uslub bahasa Arab